Development of sequential winning-percentage prediction model for badminton competitions: applying the expert system sequential probability ratio test - Jo, E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study developed a sequential winning-percentage prediction model for badminton competitions using the expert system sequential probability ratio test (EXSPRT), aiming to calculate the difficulty of each event within a match and establish the initial prior probability.